Analysis and optimal control of susceptible latent-breaking-out-countermeasure computer virus model / Mohammed Salem Mohammed Babusail - Mohammed Salem , Mohammed Babusail (2019)
Nowadays, our lives rely significantly on technologies and communications between these technologies from manufacturing industries downward to daily activities which made networks become bigger and it is continuously growing more and more where this gives viruses opportunity to spread faster causing a real threat to human. One of the methods researchers working on it to prevent spreading of viruses is to understand how these viruses propagate in a network via building mathematical models that represent virus propagation. This research project proposes a new SLBC (Susceptible-Latent-Breaking-out-Countermeasure) virus propagation model and studies its invariant, equilibrium, and stability. In addition, finds the optimal control system for the model. Lastly, some examples are presented to study virus prevalence over different conditions.